2021
DOI: 10.1016/j.scitotenv.2021.147673
|View full text |Cite
|
Sign up to set email alerts
|

Endangered Australian top predator is frequently exposed to anticoagulant rodenticides

Abstract: Anticoagulant rodenticides (ARs) used to control mammalian pest populations cause secondary exposure of predatory species throughout much of the world. It is important to understand the drivers of non-target AR exposure patterns as context for assessing long-term effects and developing effective mitigation for these toxicants. In Australia, however, little is known about exposure and effects of ARs on predators. We detected AR residues in 74% of 50 opportunistically collected carcasses of the Tasmanian wedge-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…AR poisoning was also previously detected in bald and golden eagles by Stone et al (1999). In Australia, Pay et al (2021) detected AR residues in 74% of Tasmanian wedge-tailed eagles (Aquila audax fleayi) found dead (n = 50). We detected SGARs in the only golden eagle we analysed, but every previous study of large eagles has indicated significant exposure levels varying from 25% to 100%, depending on the sampling method or location.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…AR poisoning was also previously detected in bald and golden eagles by Stone et al (1999). In Australia, Pay et al (2021) detected AR residues in 74% of Tasmanian wedge-tailed eagles (Aquila audax fleayi) found dead (n = 50). We detected SGARs in the only golden eagle we analysed, but every previous study of large eagles has indicated significant exposure levels varying from 25% to 100%, depending on the sampling method or location.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, the Convention on the Conservation of Migratory Species of Wild Animals (the CMS, or Bonn Convention) highlighted secondary exposure to ARs as one of the most important toxicological hazards for migratory birds (CMS, 2014). The high acute toxicity and persistence of ARs in animal tissues, especially of SGARs, has led to their becoming ubiquitous in rodent-predator-scavenger food webs (López-Perea and Mateo, 2018;Pay et al, 2021;Elliott et al, 2022;Cooke et al, 2022). Baits containing ARs may be consumed by a number of non-target primary consumers (e. g., invertebrates, fish, wild birds and mammals), increasing the risk of exposure across the entire food web (Shore and Coeurdassier, 2018;Regnery et al, 2020;Alabau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Under scenarios where lethal AR exposure could potentially manifest into population level effects, the impacts may be more acute for long-lived species with low reproductive rates (i.e., K-strategists), or those that are threatened or endangered where the removal of a few individuals could have marked effects on the population (Rattner et al 2014b). For example, AR exposure is of growing concern for many vulnerable species including Golden Eagles (Aquila chrysaetos; Herring et al 2017, Niedringhaus et al 2021) and Northern Spotted Owls (Strix occidentalis caurina; Gabriel et al 2018) in North America, Spanish Imperial Eagles (Aquila adalberti), Red Kites, and Common Kestrels (Falco tinnunculus; Roos et al 2021) in Europe (Howald et al 1999, van den Brink et al 2018, Nakayama et al 2019, and Wedge-tailed Eagles (Aquila audax; Pay et al 2021) in Australia. If population level effects were to occur, a decline in ecosystem functions and services provided by raptors, including scavenging (i.e., removal of carcasses from the landscape), nature-based recreation (e.g., bird watching), and biological control of rodent agricultural pests (Dona ´zar et al 2016) may ensue.…”
Section: Effects Of Rodenticides On Raptor Populationsmentioning
confidence: 99%
“…Further to this, there is growing evidence that non‐target poisoning of non‐rodent species (e.g. possums) is leading to considerable leakage of these toxins into the wider predator community, i.e., non‐rodent hunters 2,3 . Secondary poisoning and non‐target poisoning of predators is documented extensively in the northern hemisphere 12 and is also now emerging as a significant issue in Australia with recent empirical evidence in southern boobooks Ninox boobook 1 and Tasmanian wedge‐tailed eagles Aquila audax fleayi 3 demonstrating high proportions of these species having SGARs in their livers.…”
mentioning
confidence: 99%
“…possums) is leading to considerable leakage of these toxins into the wider predator community, i.e., non‐rodent hunters 2,3 . Secondary poisoning and non‐target poisoning of predators is documented extensively in the northern hemisphere 12 and is also now emerging as a significant issue in Australia with recent empirical evidence in southern boobooks Ninox boobook 1 and Tasmanian wedge‐tailed eagles Aquila audax fleayi 3 demonstrating high proportions of these species having SGARs in their livers. This was also evident in recent research on powerful owls Ninox strenua 2 whereby extensive poisoning by SGARs was detected with 83% (15 of 18) of dead powerful owls tested showing detectable levels of SGARs in their livers.…”
mentioning
confidence: 99%